Measuring efectiveness on institutional innovation perspectives in Teacher Training Institutio - Del Cid García, Carlos Javier; Vera Noriega, José Ángel; Valenzuela Saavedra, María Monserratt (Revista de Estudios y Experiencias en Educación, 2017)
The aim of this research to measure effectiveness on institutional innovation perspectives in Teacher Training Institutions using a scale. The scale is composed of four subscales: Academic Bodies, Standards, Professional Training and Participation with the purpose of analyzing prospective conditions associated with crucial training aspects considering conditions that pose legal changes raised from modifications made to the third and 73rd article of the Mexican Constitution. This is a census research in which 610 students took part in from third, fifth and seventh semester of four Teacher Training Institutions in the Sonora State, Mexico. The factor analysis of maximum likelihood with oblimin rotation, presents a greater KMO from .70 to .94. The explained variance is 43 to 73% with Cronbach alpha of .66 to .94. The effectivity parameters and reliability allow to conclude with a scale that can be used to identify the possibility and flexibility that teacher training institutions have for a pedagogical reengineering process. KEY WORDS. Normal Education, Higher Education, Institutional Assessment. doi: 10.21703/rexe.20173233482